Attentional orienting to biologically fear-relevant stimuli: data from eye tracking using the continual alternation flicker paradigm - Rosa, Pedro Joel (2012)
Snakes are thought as fear-relevant stimuli (biologically prepared to be associated with fear) which can lead to an enhanced attentional capture when compared fear-irrelevant stimuli. Inherent limitations related to the key-press behaviour might be bypassed with the measurement of eye movements, since they are more closely related to attentional processes than reaction times. An eye tracking technique was combined with the flicker paradigm in two studies. A sample of university students was gathered. In both studies, an instruction to detect changes between the pair of scenes was given. Attentional orienting for the changing element in the scene was analyzed, as well the role of fear of snakes as a moderator variable. The results for both studies revealed a significant shorter time to first fixation for snake stimuli when compared to control stimuli. A facilitating effect of fear of snakes was also found for snakes, presenting the highly fear participants a shorter a time to first fixation for snake stimuli when compared to low-feared participants. The results are in line with current research that supports the advantage of snakes to grab attention due their evo-biological significance.